Implementasi Konseling Kelompok Berbasis Humanistic Untuk Meningkatkan Kepercayaan Diri Siswa Dalam Konteks Pembelajaran Di Sekolah - Sarazumar, Vivi Khairani; Abdi, Sofyan; Hasna, Afra; Halizah, Nia; Amrullah, Amar Khoir; Ridwan, Ahmad (CV. SINAR HOWUHOWU, 2025)
This study aims to examine the implementation of humanistic-based group counseling to improve students' self-confidence. The research method uses a qualitative approach with a case study design, involving 11 8th grade students of SMPN 234 Jakarta who have low self-confidence. The counseling process includes the stages of opening, transition, core activities, and ending. The results showed a significant increase in aspects of public speaking, assertiveness, and open acceptance of criticism. An empathetic, supportive, and non-judgmental counseling environment provides space for students to recognize their potential and increase their self-confidence. This study recommends the integration of a humanistic approach in school counseling programs to support students' psychological development.